The Effect of Customer Experience and Customer Engagement Through Customer Loyalty on Sales Revenue Achievement at PT United Tractors - Permadi, Andrie; Silalahi, Sukardi (Directorate of Academic Research and Community Services, 2021)
This study aims to examine and discuss the influence of the quality of Customer Experience and Customer Engagement with the mediation of Customer Loyalty which is thought to affect repurchase intention or in other words the achievement of sales revenue as a company performance. The variables in this study were measured through the dimensions of accessibility, service competence, customer recognition, commitment, customer value, thrust, personalization, consistency, perceived quality and customer certainty to make repeat purchases. The number of respondents involved in this study were 200 respondents, all respondents were United Tractors consumers who had purchased products and services from PT United Tractors. This research is a quantitative approach that uses an instrument in the form of a questionnaire. Research data were analyzed using SEM (Structural Equation Modeling) analysis strategy with the help of SPSS and AMOS programs and the results of the analysis in this study also show that customer loyalty can mediate the effect of Customer Experience and Customer Engagement on Repurchase Intention